Self Management Education terhadap Pengetahuan dan Perilaku dalam Pengendalian Kadar Gula Darah Penderita Diabetes Melitus - Musdalipa, Musdalipa; Nurhalinah, Nurhalinah; Badrujamaludin, Asep; Kosasi, Cecep Eli; Bangun, Argi Virgona (Journal of Telenursing (JOTING), 2025)
This study aims to analyze the effect of diabetes self-management education on knowledge and behavior in controlling blood sugar levels in diabetes mellitus patients. The method used is a quasi-experiment with a two-group pretest post-test design; namely, the intervention group was given self-management education using video media and booklets, and the control group self-management education using leaflets. The results showed that the intervention group obtained a knowledge variable with a mean rank of 17.50 with a value (Z-5.097), and behavior had a mean rank of 18.42 (Z-4.993). The control group obtained a knowledge variable with a mean rank of 14.15 with a value (Z-4.131). Meanwhile, behavior has a mean rank of 19.50 (Z-4.992) with significant results. In conclusion, through video and booklet media, the intervention group substantially affects diabetes self-management education and knowledge and behavior in controlling blood suzgar levels in diabetes mellitus patients through both video media and leaflets. Keywords: Diabetes Mellitus, Blood Sugar, Self Management Education